AIDS in adults in the capital of Minas Gerais: An intervention project (Research, Society and Development, 2024)
Introduction: AIDS continues to be one of the main problems for health systems. In Brazil, even with the presence of a program that revolutionized the improvement of these patients’ life expectancy, opportunistic diseases still cause many fatalities. The objective of this article is to study and propose interventions to promote the prevention of HIV infection and the progression to AIDS. Methods: Quantitative descriptive epidemiological study of confirmed cases of AIDS in the city of Belo Horizonte/MG, from 2013 to 2023, using secondary data. A systematic review was also carried out on interventions to prevent HIV infection and the progression to AIDS published between 2013 and 2023 in the SciELO and Pubmed databases. Results: 15,170 cases of AIDS were confirmed, showing a greater drop in diagnoses from 2022 to 2023, of around 36%. The majority (39.7%) of cases were described in patients with homosexual relationships, 36.2% in the 25 to 34 age group and 76.4% living in urban areas. Still, 84.7% are alive, 935 died of AIDS and 95 of other causes. The main interventions identified through the literature review are based on health education, screening and follow-up. Conclusion: This study helps to understand that the fight against this disease still needs to expand prevention and intervention actions in the community to reduce it’s incidence and transmission.